EP326 Overexpression of SOCS-1 may inhibit invasion and metastasis of cervical cancer. (1st November 2019) - Kim, MH; Ryu, SY; Kim, BJ; Jeong, HJ; Jeong, JH
Abstract : Introduction/Background: Cervical cancer is a leading cause of cancer related deaths in women worldwide caused due to infection of high-risk human papillomaviruses. Suppressor of cytokine signaling (SOCS) family is an important negative regulator of cytokine signaling and deregulation of SOCS has been involved in many types of cancer. All cervical cancer cell lines tested showed lower expression of SOCS1, SOCS3, and SOCS5 than normal tissue or cell lines. We published that SOCS genes are silenced by DNA hypermethylation and histone deacetylation and regulate response to radiotherapy in cervical cancer cells (doi:10.1371/journal.pone.0123133). Methodology: We established stable SOCS-1-overexpressing ME-180 cell line with pLNCX2-mSOCS-1-Myc. Also we established xenograft nude mouse model for tumor growth delay experiment. Immunohistochemistry was employed to elucidate the pattern of expression of VEGF, CD-31, MMP-2, and TUNEL assay for apoptosis in SOCS-1 overexpressing ME-180 cells. Tumor cells were injected to right thigh of mouse to form cancer mass. Lung metastasis assay was performed in day 45 and 60. Metastatic nodules in both lungs were obtained and counted for statistical analysis. Results: Tumor growth delay after 5 Gy radiation was observed in SOCS-1 overexpressing tumor compared to wild type tumor but the difference did not show the statistical significance (p>0.05, Mann-Whitney U test). Immunohistochemistry showed that decreased MMP-2 expression, decreased VEGF expression, decreased CD-31 expression, and significantly elevated index of apoptotic body in SOCS-1 overexpressing tumor. Lung metastasis assay showed statistically significant decrement of metastatic nodule count in SOCS-1 overexpressing tumor (p<0.05, Mann-Whitney U test). Conclusion: Decrement of radiosensitivity was statistically insignificant in SOCS-1 overexpressing tumor while invasion, angiogenesis, and metastasis were inhibited. Also apoptosis was increased in SOCS-1 overexpressing tumor. Disclosure: Nothing to disclose.